FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN TELEKOMUNIKASI DI INDONESIA - Jantu Sukmaningtyas; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2011)
The purpose of this thesis is to analyze factors that influence capital structure at telecommunications industry in Indonesia. In this research, dependent variable is capital structure and the independent variables are the operating leverage, taxes, and firm size.The samples are 5 companies, its take by purposive sampling method: taking the sample with specific criteria, that is the companies which listed on the Indonesia Stock Exchange during the period from 2005 to 2009. The operating leverage has a positive and significant influence to capital structure, tax has a negative and significant impact to capital structure, but the variable firm size has no effect to capital structure.